Critical success factors of strategy-led planning of high-profile projects - Ramanayaka, Chamil Erik; Olatunji, Oluwole; Rotimi, J.O. (2020)
This study investigates the relationship between project strategies and project outcomes. Technical rationality theory is critical to this relationship; although it has been criticised in extant studies for its inability to define soft issues that associate with real-world scenarios. Strategy-led approach is an alternative to technical rationality. Normative studies have acknowledged the ability of strategy-led approach to project implementation as though it facilitates reflective interaction with problem-solving. This study targeted 154 organizations that won practice excellence awards of the New Zealand Institute of Building’s (NZIOB) between 2001 and 2014. The awards are given to construction firms, adjudged through a rigorous competitive process as the most outstanding in the successful completion of high-profile projects in New Zealand. 40 valid responses from construction managers who completed projects that won NZIOB’s practice excellence awards were analysed to evaluate the impact of strategies on project objectives. In addition, 35 critical success factors explored from literature were considered for statistical analysis. Findings from regression analyses show project strategies impacted 13 critical success factors that significantly shaped cost, time and quality outcomes of award winners’ projects. Negative impact of critical success factors was reported also. The study concludes that construction managers rely on project strategies as projects became increasingly challenging; the systems approach developed from such success-driven practices will benefit both the research and practice communities as they seek ways to optimise project success.